Challenges in Developing Teaching Materials Faced by English Teachers at SMPN 1 Waru - Aura, Carizza Nafta; Madjid, Hilda Izzati; Lukmansono, Toto (ICONELT, 2024)
This study investigates the challenges faced by English teachers at SMPN 1 Waru in developing teaching materials. Interviews with two participants revealed that teachers prioritize selecting materials that cater to student's needs and learning styles and that materials should be engaging and easy to understand. However, student motivation, students' lack of knowledge, and teacher struggles with technology pose significant challenges. The findings align with previous research on difficulties encountered in teaching English in junior high schools. This study highlights specific challenges, such as students' lack of English skills and reading reluctance, alongside teacher difficulties integrating technology. The study suggests a multifaceted approach to address these challenges. This includes ensuring materials align with students' learning styles and proficiency levels while also being engaging and easy to understand. Motivation is identified as a crucial factor in student success, particularly in reading. Future research areas could explore the impact of professional development programs designed to enhance teacher technological skills and develop frameworks for selecting teaching materials that cater to diverse student needs. Longitudinal studies examining the long-term effects of these strategies and further investigation into student motivation are also recommended. This research contributes to developing more effective English language teaching practices in junior high schools, ultimately leading to improved educational outcomes.